2014
DOI: 10.2169/internalmedicine.53.0514
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Intensive Immunosuppressive Therapy for Treating Simultaneously Occurring Cerebral Lesions and Pulmonary Arterial Hypertension in a Patient with Systemic Lupus Erythematosus

Abstract: A 59-year-old woman who had been diagnosed with systemic lupus erythematosus (SLE) was admitted to our hospital due to paralysis in all of her limbs. The patient presented with dysarthria, cerebellar ataxia and hypoxia. Magnetic resonance imaging (MRI) revealed vasogenic edema in the brain stem and the cerebellum. She was diagnosed with neuropsychiatric lupus syndrome (NPSLE) and pulmonary arterial hypertension (PAH), and was successfully treated using immunosuppressive therapy. To our knowledge, this is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, CTD-PH also has characteristics of Group 1’ (pulmonary vein occlusion), Group 2 (pulmonary hypertension due to left sided heart disease), and Group 3 (pulmonary hypertension due to lung diseases) because it sometimes accompanies pulmonary vein occlusion, fibrosis of the left ventricular myocardium, and interstitial pneumonia. Further, CTD-PH, except in case of scleroderma, can be expected the improvement by immunosuppressive therapy [ 1 , 7 ], which is another way in which CTD-PH differs from IPAH. Thus, to approach clinical CTD-PH, an experimental model of CTD that spontaneously develops pulmonary hypertension is necessary in addition to monocrotaline-administered mice and vascular endothelial growth factor (VEGF) inhibition with hypoxic exposure mice which are popular as animal models of pulmonary arterial hypertension [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, CTD-PH also has characteristics of Group 1’ (pulmonary vein occlusion), Group 2 (pulmonary hypertension due to left sided heart disease), and Group 3 (pulmonary hypertension due to lung diseases) because it sometimes accompanies pulmonary vein occlusion, fibrosis of the left ventricular myocardium, and interstitial pneumonia. Further, CTD-PH, except in case of scleroderma, can be expected the improvement by immunosuppressive therapy [ 1 , 7 ], which is another way in which CTD-PH differs from IPAH. Thus, to approach clinical CTD-PH, an experimental model of CTD that spontaneously develops pulmonary hypertension is necessary in addition to monocrotaline-administered mice and vascular endothelial growth factor (VEGF) inhibition with hypoxic exposure mice which are popular as animal models of pulmonary arterial hypertension [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regimen of IVCY for SLE- or MCTD-associated PAH also remains to be established. In previous studies and case reports, the dose, interval, and duration of IVCY for SLE- or MCTD-associated PAH were 500 to 1,000 mg/m 2 per pulse, monthly in most cases, and 3 to 12 months, respectively ( 1 , 3 - 5 , 8 - 17 ).…”
Section: Discussionmentioning
confidence: 92%
“…6 Watanabe et al similarly described a slight alteration in mental status that was associated with imaging findings that showed cerebellar edema. 14 However, Sy et al reported symptoms include headache, visual hallucinations, and disorientation while having unremarkable MRI findings. 11 In our case, MRI did not provide any definitive cause for our patient’s disorientation.…”
Section: Discussionmentioning
confidence: 99%